Strain effects on central hemodynamics and cardiovascular load indices in elite archers - Tambovtseva, R. V.; Orel, V. R. (Theory and Practice of Physical Culture, 2017)
Objective of the study was to analyze strain effects on central hemodynamics and cardiovascular load indices in elite archers. The central hemodynamics indices including stroke volume (SV), cardiac output (CO), heart rate (HR) and key phases of cardiac cycle were obtained using tetrapolar rheography. We applied special software tools to compute elastic (Ea) and peripheral (R) vascular resistance rates based on the systolic and diastolic blood pressure indices. The study data showed that the vascular resistance indices vary in a wide range from the optimal/ normal levels to sub-hypertonic and hypertonic rates, with the systolic and diastolic blood pressure staying within the normal range prior to and in the expander drawing phases and in the recovery phase. The stroke volume and minute rates were found to significantly fall with growth of the vascular resistance rates.